An exploration of the bone health of older adults with an intellectual disability in Ireland - Mc Carron, Mary; Burke, Eilish (My University, 2017)
Background: Many risk factors have been confirmed for poor bone health among the general population including age, gender and corticosteroid use. There is a paucity of investigation among people with intellectual disability; however, research points to differing risks namely anti-epileptic medication use, Down syndrome and poor behaviour lifestyle. Methods: Data was extracted from the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing in Ireland. In total, 753 participants took part, and data was gathered on participants' health status, behavioural health, health screenings and activities of daily living. The prevalence of osteoporosis and related risk factors were specifically examined. Results: Overall, 8.1% reported a doctor's diagnosis of osteoporosis with over 20% reporting history of fracture. Risk identified included older age (P < 0.0001), female gender (P < 0.0001), difficulty walking (P < 0.0001) with older age and being female the stronger predictors for osteoporosis, odds ratio = 6.53; 95% confidence interval 2.82–15.11 and odds ratio = 4.58; 95% confidence interval 2.29–9.17, respectively. There was no gender difference regarding the level of fractures; however, epilepsy and anti-epileptic medication were strong predictors. Overall, 11.1% attended for bone screening diagnostics. Conclusion: Despite low levels of reported doctor's diagnosis of osteoporosis risk factor prevalence was high. Considering the insidious nature of osteoporosis and the low levels of diagnostic screening, prevalence could be possibly higher.
PUBLISHED
Keywords: Intellectual Disability; Health